2010
DOI: 10.1098/rspb.2010.0584
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal extinction dynamics in a freshwater cetacean

Abstract: Geographical range contraction is a fundamental ecological characteristic of species population decline, but relatively little investigation has been conducted into general trends in the dynamic properties of range collapse. The Yangtze River dolphin or baiji (Lipotes vexillifer), probably the first large mammal species to have become extinct in over 50 years, was believed to have experienced major range collapse during its decline through progressive large-scale range contraction and fragmentation. This range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 32 publications
2
53
1
Order By: Relevance
“…Further interview data show that porpoises may undergo seasonal upstream-downstream movements, possibly in response to the annual high-low water cycle. Although mtDNA genetic structuring shown by porpoise samples from the middle-lower Yangtze has been interpreted to suggest these animals may not move far (Zheng et al, 2005), informant data have previously demonstrated that baiji formerly also made large-scale upstream-downstream movements (Zhang et al, 2003;Turvey et al, 2010b). Seasonal movements may also explain the slight spatial shift in peak porpoise abundance along the river shown between informant weekly sighting data and autumn 2006 boat-based survey data.…”
Section: Discussionmentioning
confidence: 92%
“…Further interview data show that porpoises may undergo seasonal upstream-downstream movements, possibly in response to the annual high-low water cycle. Although mtDNA genetic structuring shown by porpoise samples from the middle-lower Yangtze has been interpreted to suggest these animals may not move far (Zheng et al, 2005), informant data have previously demonstrated that baiji formerly also made large-scale upstream-downstream movements (Zhang et al, 2003;Turvey et al, 2010b). Seasonal movements may also explain the slight spatial shift in peak porpoise abundance along the river shown between informant weekly sighting data and autumn 2006 boat-based survey data.…”
Section: Discussionmentioning
confidence: 92%
“…Loss of the Ganges river dolphin from Nepal would be disturbing considering the previous loss of the Yangtze river dolphin (Turvey et al . ). Predictions for loss of the Ganges River dolphin have been made previously.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the most cautionary example is that of the recent (functional) extinction of the Yangtze River dolphin ( Lipotes vexillifer ) [52], which represents the first known cetacean extinction in recent history.…”
Section: Discussionmentioning
confidence: 99%